Contribution of BubR1 to oxidative stress‐induced aneuploidy in p53‐deficient cells. (26th June 2013) - Ikawa‐Yoshida, Ayae; Ando, Koji; Oki, Eiji; Saeki, Hiroshi; Kumashiro, Ryuichi; Taketani, Kenji; Ida, Satoshi; Tokunaga, Eriko; Kitao, Hiroyuki; Morita, Masaru; Maehara, Yoshihiko
Abstract DNA aneuploidy is observed in various human tumors and is associated with the abnormal expression of spindle assembly checkpoint (SAC) proteins. Oxidative stress (OS) causes DNA damage and chromosome instability that may lead to carcinogenesis. OS is also suggested to contribute to an increase in aneuploid cells. However, it is not clear how OS is involved in the regulation of SAC and contributes to carcinogenesis associated with aneuploidy. Here we show that an oxidant (KBrO3) activated the p53 signaling pathway and suppressed the expression of SAC factors, BubR1, and Mad2, in human diploid fibroblast MRC5 cells. This suppression was dependent on functional p53 and reactive oxygen species. In p53 knockdown cells, KBrO3 did not suppress BubR1 and Mad2 expression and increased both binucleated cells and cells with >4N DNA content. BubR1 and not Mad2 downregulation suppressed KBrO3‐induced binucleated cells and cells with >4N DNA content in p53 knockdown cells, suggesting that BubR1 contributes to enhanced polyploidization by a mechanism other than its SAC function. In analysis of 182 gastric cancer specimens, we found that BubR1 expression was significantly high when p53 was positively stained, which indicates loss of p53 function (P = 0.0019). Moreover, positive staining of p53 and high expression of BubR1 in tumors were significantly correlated with DNA aneuploidy (P = 0.0065). These observations suggest that p53 deficiency may lead to the failure of BubR1 downregulation by OS and that p53 deficiency and BubR1 accumulation could contribute to gastric carcinogenesis associated with aneuploidy.